Bediom Tradition in Cultivating Social Care Character Education Values in the Lampung Saibatin Community, West Lampung Regency - Haris Budiman; Dendi Ari Sulendra; Ainur Rofiq (Anjasmoro)
Lampung society is known as a society that adheres to tradition in treading the reality of its social life, including the Bediom tradition. Bediom is the culture and customs of the Lampung people, especially the coastal Indigenous people who will move house (moving lamban) either a newly built house or a house that has been standing for a long time and will be occupied by new residents. This study aims to analyze the Implementation of the Bediom tradition in fostering the value of social care character education and why the Bediom tradition is still carried out today by the Lampung people. This research is a type of qualitative research using a social construction approach. This research was conducted in Turgak village, Belalau sub-district, West Lampung district. Data collection was carried out utilizing observation, document collection, and interviews. Data sources include interviews with traditional leaders, community leaders, and religious leaders. The results of this study indicate that the implementation of the Bediom tradition in fostering the value of social care character education in the Lampung Saibatin community is very good and has many positive impacts. And can foster the value of social care character education including 1) mutual cooperation, 2) respect, 3) being grateful, and 4) togetherness. There are several reasons why the Bediom tradition is still carried out today by the Lampung Saibatin community including 1) The Bediom tradition is one of the identities of the Lampung Saibatin community, West Lampung Regency, 2) As a form of appreciation and respect for ancestors, 3) To maintain the sacredness of the implementation of the Bediom tradition, 4) The Bediom tradition can keep up with the times.